1989
DOI: 10.1038/340646a0
|View full text |Cite
|
Sign up to set email alerts
|

Qa-1 restricted recognition of foreign antigen by a γδ T-cell hybridoma

Abstract: Distinct T-lymphocyte subsets recognize antigens in conjunction with different classes of major histocompatibility complex (MHC) glycoproteins using the T-cell receptor (TCR), a disulphide-linked heterodimer associated with the CD3 complex on the cell surface. In general, class I and class II MHC products provide a context for the recognition of foreign antigens by CD8+ and CD4+ T cells, respectively. This recognition seems to be largely dependent on alpha beta TCR heterodimers, whereas the function of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(110 citation statements)
references
References 35 publications
6
102
2
Order By: Relevance
“…Most prominently, a response of a cd hybridoma to poly GT, a polymer of approximately 100 amino acids containing glutamic acid and tyrosine at a 1 : 1 ratio, was published as early as 1989. 97 We later showed that essentially all Vc1 1 cd T cells respond to poly GT, 18 as well as cells expressing other cd TCRs, but we were unable to confirm the original claim that poly GT is recognized in the context of Qa-1 b . With its random sequence, poly GT is not a defined Ag and does not have a defined structure.…”
Section: Smaller Peptidescontrasting
confidence: 58%
“…Most prominently, a response of a cd hybridoma to poly GT, a polymer of approximately 100 amino acids containing glutamic acid and tyrosine at a 1 : 1 ratio, was published as early as 1989. 97 We later showed that essentially all Vc1 1 cd T cells respond to poly GT, 18 as well as cells expressing other cd TCRs, but we were unable to confirm the original claim that poly GT is recognized in the context of Qa-1 b . With its random sequence, poly GT is not a defined Ag and does not have a defined structure.…”
Section: Smaller Peptidescontrasting
confidence: 58%
“…The increase required ␤ 2 M and TAP-1 expression, implying that the affected V␥4 ϩ T cells respond to MHC class I or related molecules. With the possible exception of Qa-1 b -reactive cells (30), all MHC class I-specific murine ␥␦ T cells characterized thus far express V␥4 (31)(32)(33)(34). This survey suggests that the V␥4 ϩ T cell subset is biased toward MHC class I recognition.…”
Section: Discussionmentioning
confidence: 97%
“…Anti-Qa-1 Abs have been shown to block recognition of the copolymer Glu 50 -Tyr 50 by a ␥␦ T cell hybridoma (27). Tompkins et al (28) demonstrated that Qa-1 b -restricted T cell hydribomas generated by immunizing low-responder H-2 b mice with pork insulin recognize an insulin B chain determinant in a TAP-independent fashion.…”
mentioning
confidence: 99%